Kesiagaan Pustakawan Dalam Menghadapi Bencana (Disaster Planning) Di Perpustakaan Institut Seni Indonesia Surakarta - Ika Laksmiwati; M. Ali Nurhasan Islamy (Tibanndaru : Jurnal Ilmu Perpustakaan dan Informasi, 2020)
The purpose of this study is to find out how librarians are prepared to deal with disasters (Disaster Planning) from biological factors (termites) and fire disasters in the Library of Indonesia Institute of the Arts of Surakarta. Various library threats or library assets from damage can be threats from natural disasters such as earthquakes, volcanic eruptions, floods, tsunamis, fires, and so on. Other damage threats can be caused by biological and chemical and human factors, such as theft, vandalism, and the like. This study uses a qualitative research approach, namely research that describes the phenomenon, digging data by interviews, observation, and documentation. Problems in qualitative research are still temporary, tentative, and will develop or change after the researcher is in the field. Qualitative research requires data sources from informants. The use of triangulation techniques is done to test the credibility of the data by checking the data to the same source with different techniques. For example, data obtained by interview, then checked by observation, documentation, or questionnaire. Good planning in dealing with disasters will reduce the impact, including preparedness and long-term risk reduction measures. Matthews (2009) states that there are several steps or stages in disaster planning, including 1) prevention, 2) responses. The results of this research could theoretically contribute to scientific treasures for librarians in dealing with disasters (Disaster Planning) in the library. Besides, it is an input or recommendation and thought for the Indonesian Institute of the Arts of Surakarta.Keywords: librarian’s alert, disaster planning, biological (termite), fire